Ubezpieczenie chorobowe w Republice Federalnej Niemiec i reformy z roku 1989 i 1993 - Zerche, Jürgen (Wydział Prawa i Administracji UAM, 1994)
The author presents a synthetic overview of the economic, social and technical aspects of the organisation of medical insurance in the Federal Republic of Germany and the reforms carried out in the last decade. VaHous costs related to different solutions of the problem of social welfare in the scope of health care have been analysed in detail.
Medical Insurance in the Federal Republic of Germany vs reforms in 1989 and 1993